Christianity under the Ancien Régime, 1648-1789 - Ward, W. Reginald (William Reginald) (New approaches to European history., 1999)
In the middle of the seventeenth century religious belief and practice were intrinsic parts of everyday life and very difficult to escape. Professor Ward offers a brief, but comprehensible, account of Christianity in Europe between the Westphalia settlements 1648 and the French Revolution in 1789. The focus of the book, however, is not on the religious institutions themselves, but on policy, that is to say those things which conservatives and reformers, revivalists and missionaries, statesmen and peasants sought to change or preserve in their religious heritage. Within each chapter the political, social and intellectual events and influences of the times are discussed, thus allowing the reader to understand changes in policy in context.